Genetic Susceptibility to Autoimmune Disorders: Clues from Gene Association and Gene Expression Studies - Gutierrez-Roelens, Ilse; Lauwerys, Bernard R. (Current Molecular Medicine, 2008)
Susceptibility to autoimmune disorders results from the interaction of multiple genetic factors that regulate the threshold of autoreactivity. Genome-wide microsatellite screens and large-scale single nucleotide polymorphism (SNP) association studies have identified chromosomal loci that are associated with specific disorders including systemic lupus erythematosus, rheumatoid arthritis, juvenile arthritis, multiple sclerosis, and diabetes. Numerous candidate gene association studies have in turn investigated the association of specific genes within these chromosomal regions, with susceptibility to autoimmune diseases (e.g. FcgammaReceptors, TYK2 and systemic lupus). More recently, large-scale differential gene expression studies performed on selected tissues from patients with autoimmune disorders, have led to the identification of gene signatures associated with the activation of specific pathways in these diseases (e.g. interferon signature in lupus). In the future, integrated analyses of gene (and protein) expression together with SNP data will allow us to sketch an intelligible picture of the genesis of autoimmunity in humans. This review sets out to illustrate how the most recent advances in the field of systemic lupus erythematosus, rheumatoid arthritis and juvenile arthritis have led to a better understanding of these disorders.
Keywords: gene expression